Estudo da fadiga de contato em engrenagens cilíndricas de dentes retos - Koda, Fábio (2009)
Due to the resistance of automotive manufactures on apply ADI gear studies have been made to verify the performance of this material. Inside this context this work has a main objective the construction of contact fatigue test machine in gears and the comparison, related to the wear resistance, between spur-gears made of carburized and quenched AISI 8620 low steel and austempered ductile iron (ADI). These gears were supplied in two states of finish surface (by shaving or by machining). The developed equipment functions with the principle of the power recirculation and commonly called FZG. The wear experiments were performed in two stages of torque: 135 N.m (running-in) and 302 N.m (steady-state) and the gears have modified profile. After the accomplishment of the experiments, was possible verify that: (1) The damaged area of flanks, due to the phenomenon of pitting, at ADI gears was bigger than AISI 8620 low-alloy steel gears. (2) The comparisons between the roughness parameter in the supply state and after each period of the experiment shows that gears with surface finish by shaving have better load distribution and minor wear. (3) Lubricant regime at pitch diameter was the boundary for both manufacture process, but the film thickness parameter λ is higher for shaved gears, making the lubricant film thickness has major value, (4) The reduction effect the resistive area of contact due the presence of the graphite nodules in the contact fatigue resistance was evidenced, however surface finishing was more relevant than the distribution and size nodules.